On the appearance of a Hopf bifurcation in a non-ideal mechanical problem - Dantas, MJH; Balthazar, José Manoel [UNESP] (Elsevier B.V., 2003)
In this paper we studied a non-ideal system with two degrees of freedom consisting of a dumped nonlinear oscillator coupled to a rotatory part. We investigated the stability of the equilibrium point of the system and we obtain, in the critical case, sufficient conditions in order to obtain an appropriate Normal Form. From this, we get conditions for the appearance of Hopf Bifurcation when the difference between the driving torque and the resisting torque is small. It was necessary to use the Bezout Theorem, a classical result of Algebraic Geometry, in the obtaining of the foregoing results. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Hopf bifurcation; non-ideal problems; center manifold